EMOTIONAL ABUSE AS HUMAN INSECURITY: A MYTH OR REALITY? Received: 31st August 2021; Revised: 15th December 2021, 19th February 2022; Accepted: 23rd February 2022 - Alade , Adebola Afolake; Ala, Modupe Oziofu (PEOPLE: International Journal of Social Sciences, 2022)
The paper is focused on emotional abuse on both genders in intimate relationships as human insecurity, how it is being under-reported and perceived by many in the Nigerian society as an insignificant issue since it is not physical, and where many are advised to bear it in silence or even accused of being the cause of it most of the times. The study examines the signs, causes, and effects, which makes it a form of human insecurity. The study is anchored on Attachment Theory. Secondary data were employed in gathering information and content data analysis was used in analysing the data for the study. The paper concluded that emotional abuse is a reality that many are not accepting and that speaking out to the right people (such as talking to trusted family members, friends, associates and therapists) is the first and main strategy in which the problem can be solved.